CFD-single particle modeling and simulation of the removal of H2S in a packed-bed bioreactor. Issue 4 (August 2021) - Xie, Le; Zhu, Jundong; Ramírez, Martín; Jiang, Chongwen
Abstract: In this study, a single particle model coupled with a computational fluid dynamics (CFD) model was developed to simulate the mass transfer-biodegradation process in a packed-bed bioreactor for the removal of H2 S. Sensitivity analyses of particle size and diffusion coefficient were performed to evaluate their effects on internal diffusion on a single particle scale. The role of the liquid phase was evaluated on the reactor scale. The developed CFD coupled model was then validated by comparing the simulation results to experimental data in terms of removal efficiency at different inlet loads of H2 S. A gradual reduction of the internal diffusion effect was observed with increase in the inlet H2 S concentration, and internal diffusion had a minor influence on the removal efficiency when the particle size was less than 2.5 mm. The proposed CFD coupled model is potentially a useful tool to investigate the mass transfer-biodegradation behaviors in packed-bed bioreactors with complicated multiscale properties. Graphical Abstract: ga1 Highlights: CFD simulation is an effective tool for guiding engineering application. Internal diffusion effect can be ignored when particle size was less than 2.5 mm. Simulation results are beneficial to the scale-up of bioreactors for H2 S treatment. Investigation of the role of internal diffusion from multiscale perspective.